KAJIAN AKADEMIK TENTANG USAHA PENGINAPAN HOTEL MELATI, GUEST HOUSE DAN KOST KOTA SAMARINDA - Fatimah Asyari; Amin Slamet; Maisyarah . (Universitas 17 Agustus 1945 Samarinda, 2022)
Academic studies on business arrangements for budget hotels, guest houses and boarding houses are carried out as a form of formulating or identifying legal problems that arise related to the booming business of budget hotels, guest houses and boarding houses in Samarinda City.The stages of the study carried out in a coherent and orderly manner are: (1) Identification of problems related to business arrangements for jasmine hotels, guest houses and boarding houses; (2) Inventory of required legal materials related to business regulations for jasmine hotel lodging, guest houses and boarding houses; (3) Systematization of Legal Materials; and (4) Analysis of legal materials.The number of jasmine hotel lodgings, guest houses and boarding houses in the city of Samarinda is relatively large, in practice jasmine hotel lodgings, guest houses and boarding houses are in some cases used by irresponsible people to support prostitution / online prostitution or free sex, child trafficking minors, drug abuse. Then, the existence of jasmine inns, guest houses and boarding houses also reaped reactions from five-star hotel entrepreneurs who indicated that the existence of jasmine hotel inns, guest houses and boarding houses had an economic impact that threatened hospitality investment.Special arrangements in the form of Regional Regulations regarding Business Arrangements for Budget Hotels, Guest Houses and Boarding Houses need to be established immediately. The urgency of the establishment of a Regional Regulation concerning Business Arrangements for Budget Hotels, Guest Houses and Boarding Houses is to ensure legal certainty and protection, peace and social order for the community as well as a legal umbrella for the implementation of all forms of efforts related to Business Arrangements for Budget Hotels, Guest Houses and Boarding Houses in Indonesia. Samarinda City.